Pio Gama Pinto : Kenya's unsung martyr : 1927-1965 - Durrani, Shiraz (Vita Books, 2018)
Pio Gama Pinto was born in Kenya on March 31, 1927. He was assassinated in Nairobi on February 24, 1965. In his short life, he became a symbol of anti-colonial and anti-imperialist struggles in Kenya and India. He was actively involved in Goa's struggle against Portuguese colonialism and in Mau Mau during Kenya's war of independence. For this, he was detained by the British colonial authorities in Kenya from 1954-59. His contribution to the struggle for liberation for working people spanned two continents - Africa and Asia. And it covered two phases of imperialism - colonialism in Kenya and Goa and neo-colonialism in Kenya after independence. His enemies saw no way of stopping the intense, lifelong struggle waged by Pinto - except through an assassin's bullets. But his contribution, his ideas, and his ideals are remembered and upheld even today by people active in liberation struggles. This book does not aim or claim to be a comprehensive record on Pio Gama Pinto, just the beginning of the long journey necessary to record the history of Kenya from an anti-imperialist perspective. It introduces readers to voices of many people who have written about Pinto to build up as clear a picture of Pinto as possible. In that spirit, it seeks to make history available to those whose story it is - people of Kenya, Africa and progressive people around the world. [back cover].